New species of Simothraulopsis Demoulin, 1966 (Ephemeroptera: Leptophlebiidae) from Northeastern Region of Brazil - Lima, Lucas R. C. (Zootaxa, 2018)
Simothraulopsis Demoulin, 1966 is a Neotropical genus of Leptophlebiidae with nine species known from South America. In the present paper, based on male imagos from the northeastern region of Brazil in the states of Alagoas and Piauí, two new species of the Simothraulopsis are described: Simothraulopsis sinuosus sp. nov. and Simothraulopsis gracilianus sp. nov.